2015
DOI: 10.1111/1462-2920.13086
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory quinones in Archaea: phylogenetic distribution and application as biomarkers in the marine environment

Abstract: The distribution of respiratory quinone electron carriers among cultivated organisms provides clues on both the taxonomy of their producers and the redox processes these are mediating. Our study of the quinone inventories of 25 archaeal species belonging to the phyla Eury-, Cren- and Thaumarchaeota facilitates their use as chemotaxonomic markers for ecologically important archaeal clades. Saturated and monounsaturated menaquinones with six isoprenoid units forming the alkyl chain may serve as chemotaxonomic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 84 publications
(143 reference statements)
5
71
1
Order By: Relevance
“…S4b). We interpreted these results as an indication that MPh species synthesized by M. mazei and M. acetivorans have two saturated prenyl moieties on the pentaprenyl tail, whereas that from M. barkeri has only one saturated prenyl moiety, confirming the MPh prenyl tail saturation reported by others (31). Archaea and bacteria adjust the quantity of membrane soluble electron carriers during batch growth.…”
Section: Resultssupporting
confidence: 86%
“…S4b). We interpreted these results as an indication that MPh species synthesized by M. mazei and M. acetivorans have two saturated prenyl moieties on the pentaprenyl tail, whereas that from M. barkeri has only one saturated prenyl moiety, confirming the MPh prenyl tail saturation reported by others (31). Archaea and bacteria adjust the quantity of membrane soluble electron carriers during batch growth.…”
Section: Resultssupporting
confidence: 86%
“…Additionally, in contrast to the high diversity of respiratory quinones in related members of the Thermoplasmatales (34,73,74), no quinones were detected in M. luminyensis. Similarly, no methanophenazines, respiratory quinone analogues found in Methanosarcinales (34,75) and Methanosaeta (76) were detected in M. luminyensis. This finding supports studies by Lang et al (20) and Söllinger et al (15), who suggested that the biochemistry of methanogenesis in Methanomassiliicoccales may be fundamentally different from that in other, methanophenazine-and cytochrome-containing methylotrophic archaea.…”
Section: Lipid Inventory Of M Luminyensis Compared To Other Archaeamentioning
confidence: 73%
“…(9). Additionally, in contrast to the high diversity of respiratory quinones in related members of the Thermoplasmatales (34,73,74), no quinones were detected in M. luminyensis. Similarly, no methanophenazines, respiratory quinone analogues found in Methanosarcinales (34,75) and Methanosaeta (76) were detected in M. luminyensis.…”
Section: Lipid Inventory Of M Luminyensis Compared To Other Archaeamentioning
confidence: 88%
See 2 more Smart Citations